ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT PELABUHAN INDONESIA III (PERSERO) CABANG BANJARMASIN - Achmad Zakaria; Muhammad Riza Firdaus (Universitas Lambung Mangkurat, 2017)
The purpose of this study was to analyze the quality of service through the variable tangible, responsiveness, reliability, assurance, and empathy, to customer satisfaction PT. Pelabuhan Indonesia III (Persero) Branch of Banjarmasin. This study is a qualitative study using data from questionnaires completed by a sample of 150 samples of the total number of service users PT. Pelabuhan Indonesia III (Persero) Branch of Banjarmasin period from January to June 2015. The sampling technique used purposive sampling technique, with testing through Test f, t Test and Test Coefficient of Determination (R2). The results showed that partially and simultaneously, the five dimensions of service quality that is tested through variable tangible, responsiveness, reliability, assurance, and empathy, influence on customer satisfaction PT. Pelabuhan Indonesia III (Persero) Branch of Banjarmasin with level of significant 5%.